High Efficiency Light Harvesting by Carotenoids in the LH2 Complex from Photosynthetic Bacteria: Unique Adaptation to Growth under Low-Light Conditions - Magdaong, Nikki M. (American Chemical Society, 2014)
[Image: see text] Rhodopin, rhodopinal, and their glucoside derivatives are carotenoids that accumulate in different amounts in the photosynthetic bacterium, Rhodoblastus (Rbl.) acidophilus strain 7050, depending on the intensity of the light under which the organism is grown. The different growth conditions also have a profound effect on the spectra of the bacteriochlorophyll (BChl) pigments that assemble in the major LH2 light-harvesting pigment–protein complex. Under high-light conditions the well-characterized B800-850 LH2 complex is formed and accumulates rhodopin and rhodopin glucoside as the primary carotenoids. Under low-light conditions, a variant LH2, denoted B800-820, is formed, and rhodopinal and rhodopinal glucoside are the most abundant carotenoids. The present investigation compares and contrasts the spectral properties and dynamics of the excited states of rhodopin and rhodopinal in solution. In addition, the systematic differences in pigment composition and structure of the chromophores in the LH2 complexes provide an opportunity to explore the effect of these factors on the rate and efficiency of carotenoid-to-BChl energy transfer. It is found that the enzymatic conversion of rhodopin to rhodopinal by Rbl. acidophilus 7050 grown under low-light conditions results in nearly 100% carotenoid-to-BChl energy transfer efficiency in the LH2 complex. This comparative analysis provides insight into how photosynthetic systems are able to adapt and survive under challenging environmental conditions.